Music Composition “Kala Senja” (Melody Variation Overview) - Elbana Duta Perwira (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2022)
The musical "Kala Senja" is an expression of the composer's feelings and memories from his childhood. This melody variation has 4 reviews of melodic variations, namely; Melodic Variation and Fake namely, Rhytmyc Variation and Fake, Dead Spot Filler, Counter Melody. The purpose of the creation of this work is as a means to achieve the goals of character education for ancient children with millennials in a musical work and as a creation of artistic texts or social texts about the character of ancient children with millennial times in a musical work. The method of finding the focus of the work can be done as an initial stimulus. An initial stimulus can be defined as something that evokes thoughts, enthusiasm or encourages activity. The stimuli for a composition can be in the form of auditive (hearing), visual (seeing), kynesthetic (movement), tactile and musical ideas from something that becomes an experience. The type of initial stimulation is in the form of visual and audio stimuli. Composers make a piece of music by describing the composer's feelings when he was a child. There are 4 parts in this piece of music. The first part of this composition is an expression of the composer's feelings of pleasure. In the second part is the composer's sad feelings. In the third part is an expression of the composer's angry feelings. The fourth part is the composer's tired feeling. This composition uses an ensemble format. The composer uses a string section with the hope that the composer can enrich the harmony and melody in the musical "Kala Senja", so that this piece of music will sound melodic and harmonious. The percussion ensemble format in this piece of music is used to provide detailed rhythmic patterns, so that apart from sounding melodic and harmonious, it also has many varied rhythms.